Trophic ecology of the Atlantic Forest endemic tree frog Boana bischoffi (Boulenger, 1887) (Anura, Hylidae) - Pereira, Gabriela de Araujo; Haddad, Celio F. B. [UNESP]; Sturaro, Marcelo Jose (Pensoft Publishers, 2023)
Studies of natural history are important to accumulate knowledge about aspects of diet, reproduction, and habitat use, which can assist the conservation biology for endangered groups, such as amphibians. Here we evaluated the trophic ecology and sexual size dimorphism of Boana bischoffi, a widely distributed and endemic tree frog species of the Brazilian Atlantic Forest. We analysed 80 individuals, covering the distribution of the species and combined our data-set with data from the literature. Gastrointestinal items were separated, accounted, and identified to the highest possible taxonomic resolution. Subsequently, the size and mass of prey items were measured. Afterwards, we calculated rates of relative importance for each prey category. The items of greatest relative importance were beetles (Coleoptera), termites (Isoptera), crickets (Orthoptera) but also harvestmen (Opiliones). We did not find a relation between female snout-vent length, mouth width and length with prey length. In males, the mouth length and width are related to prey length. We found a sexual dimorphism in size typical for hylid frogs, with females being larger than males. Our data expand the knowledge about the alimentary biology of B. bischoffi, but further research focusing on other aspects of the natural history such as possible intersexual dietary divergence and food niche overlapping, environmental prey availability and selection is still needed.
Keywords: amphibians; diet; sexual dimorphism; trophic ecology